Prevalence and Risk Factors of Artificial Urinary Sphincter Revision in Nonneurological Male Patients. Issue 5 (29th November 2021) - Bentellis, Imad; El-Akri, Mehdi; Cornu, Jean-Nicolas; Brierre, Thibaut; Cousin, Tiffany; Gaillard, Victor; Dupuis, Hugo; Tricard, Thibault; Hermieu, Nicolas; Bertrand-Leon, Priscilla; Chevallier, Daniel; Bruyere, Franck; et al.
Abstract : Purpose: The main objective of this study was to assess the prevalence and risk factors of male artificial urinary sphincter (AUS) mechanical failures and nonmechanical failures. Materials and Methods: The charts of all male patients who underwent AUS implantation between 2004 and 2020 in 16 centers were retrospectively reviewed. Patients with neurogenic stress urinary incontinence (SUI) were excluded as well as revisions/explantations due to infections and/or erosions. The causes of revision were divided into mechanical failures (fluid loss or malfunction from any components of the AUS), nonmechanical failures (urethral atrophy, recurrence/persistence of SUI despite normally functioning device) and other (pump malposition, balloon herniation, hematoma, pain). Failure-free survival analysis was performed both for general and specific causes of revision. Predictors of mechanical and nonmechanical failures were determined by Cox proportional hazards model. Results: A total of 1, 020 patients met the inclusion criteria. After a median followup of 20 months, the estimated 5-year and 10-year overall revision-free survival was 60% and 40%, respectively. There were 214 AUS revisions: 59 (27.6%) for mechanical failures, 121 (56.5%) for nonmechanical failures and 34 (15.9%) other causes of revision. In multivariable Cox regression analysis, larger cuff size was the only predictor of overall revisions (HR=1.04 [1.01–1.07]; p=0.01) and revision for nonmechanical failure (HR=1.05 [1.02–1.09]; p=0.004). Conclusions: Half of the male AUS patients underwent device revision within the first 10 years after implantation. Nonmechanical failures are the primary cause of AUS revision in nonneurological men. Larger cuff size appears to be the main determinant of AUS revision risk.